2007
DOI: 10.1007/s00421-007-0517-5
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The upper limit of physiological cardiac hypertrophy in elite male and female athletes in China

Abstract: Physiological hypertrophy in response to physical training is important in the differentiation of physiological and pathological left ventricular hypertrophy. The goal of our study was to define the structural characteristics of the heart in Chinese athletes. Between June 2005 and August 2005, 339 (165 male, 174 female) elite Chinese athletes from 19 sports were profiled. Standard two-dimensional guided M-mode and Doppler echocardiography were employed to evaluate left ventricular morphology and function. Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 35 publications
3
25
1
1
Order By: Relevance
“…There was no significant influence of age on the ventricular mass or on the ventricular volume in the multivariate model. As in other studies,18 28 29 male gender resulted in more pronounced increase of LV EDV and LV EDM, regardless of BSA.…”
Section: Discussionsupporting
confidence: 85%
“…There was no significant influence of age on the ventricular mass or on the ventricular volume in the multivariate model. As in other studies,18 28 29 male gender resulted in more pronounced increase of LV EDV and LV EDM, regardless of BSA.…”
Section: Discussionsupporting
confidence: 85%
“…A study by Sun et al in elite Chinese athletes from a variety of sporting disciplines demonstrated that Chinese athletes exhibit LV cavity size dilatation and associated LVH of similar magnitude to Caucasian athletes 35. Of the 165 male athletes, 11.5% exhibited a LV cavity size >60 mm with a maximum diameter of 65 mm and only 3 (1.8%) athletes exhibited a wall thickness of >12 mm.…”
Section: Impact Of Ethnicity Upon Cardiovascacular Adaptation To Exermentioning
confidence: 98%
“…Some data on left ventricular (LV) M-mode measurements are available, 10,12,14,17,20,23,24,28,30,31,35,3638 while data for all the other specific structures are limited (e.g. left atrial (LA) area and volumes, right ventricular (RV) diameters, aorta) or rare (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…10,14 Numerical limitations included limited sample size (e.g. < 450 subjects) in some studies 12,28,30,31,34 and limited structures evaluated in others. 11,18–20,24,25,28,30,31 Theoretically, the sample size needed to build a nomogram should be calculated by dividing the population into age groups and assuming a minimum number (at least 80 and ideally 120 subjects) for each of the groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation